Persistence of circulating ADAMTS13-specific immune complexes in patients with acquired thrombotic thrombocytopenic purpura - Ferrari, Silvia (Ferrata Storti Foundation, 2014)
Anti-ADAMTS13 autoantibodies are the main cause of acquired thrombotic thrombocytopenic purpura. Binding of these antibodies to ADAMTS13 eventually results in the formation of antigen-antibody immune complexes. Circulating ADAMTS13-specific immune complexes have been described in patients with acquired thrombotic thrombocytopenic purpura, although the prevalence and persistence of these immune complexes over time have hitherto remained elusive. Here, we analyzed a large cohort of patients with acquired thrombotic thrombocytopenic purpura for the presence of free and complexed anti-ADAMTS13 antibodies. In the acute phase (n=68), 100% of patients had free IgG antibodies and 97% had ADAMTS13-specific immune complexes. In remission (n=28), 75% of patients had free antibodies (mainly IgG) and 93% had ADAMTS13-specific immune complexes. Free antibodies were mainly of subclasses IgG1 and IgG4, whereas IgG4 was by far the most prevalent in ADAMTS13-specific immune complexes. Comparison of ADAMTS13 inhibitor and anti-ADAMTS13 IgG (total and subclasses) antibody titers in acute phase and in remission samples showed a statistically significant decrease in all parameters in remission. Although non-significant, a trend towards reduced or undetectable titers in remission was also observed for ADAMTS13-specific immune complexes of subclasses IgG1, IgG2 and IgG3. No such trend was discernible for IgG4; IgG4 immune complexes persisted over years, even in patients who had been treated with rituximab and who showed no features suggesting relapse.